PENGARUH SENAM KAKI TERHADAP PENYEMBUHAN LUKA DIABETIK PADA PASIEN DIABETES MELLITUS DI RUANG RAWAT INAP RA1 DAN RA2 PENYAKIT DALAM RSUP. H. ADAM MALIK MEDAN - Dewi Astuti Pasaribu; Septian Mixrova Sebayang (Indonesian Trust Health Journal, 2020)
Diabetic foot ulcers (DFUs) are a serious complication of diabetes mellitus (DM) that can be slow to heal, result in repeated hospitalizations, require intense and costly treatment, and reduce the quality of life. The purpose of this study was to investigate the effect of foot exercises on wound healing in type 2 diabetic patients with a diabetic foot ulcer. Quasi-experimental study using before and after changes to wound healing in between February until May 2019.Thirty patients from an inpatient rooms with ulcers who met study criteria agreed to participate. Subjects were recruited by the researchers in the hospital where they received treatment. Data were collected using investigator-developed forms: patient information form and the diabetic foot exercises log. Patients in the intervention group received standard wound care and performed daily foot exercises for 3 week. Diabetic wound healing of the patients in the intervention were examined and measured at the 3rd weeks. To analyze and compare the data, frequency distribution, mean (standard deviation), and the paired samples t test were used. The mean of diabetic wound healing were 3.50, 2.90, and 2.40 in the study intervention group in 1st, 2nd, and 3rd weeks, respectively. Significant differences were found between diabetic wound healing in pre-test and post-test group (p=0.041). An important finding in this study was the DFU area decreased more in those who exercised more. Findings suggest foot exercises should be included in the treatment plan when managing patients with diabetic foot ulcers. Abstrak Luka kaki diabetic adalah suatu komplikasi yang serius pada diabetes mellitus dimana dapat memperlambat penyembuhan, hospitalisasi berulang, membutuhkan pengobatan yang mahal dan menurunkan kualitas hidup. Tujuan penelitian ini adalah untuk mengetahui efek senam kaki terhadap penyembuhan luka pada pasien diabetes mellitus tipe 2. Jenis penelitian Quasi eksperimen digunakan untuk melihat perubahan sebelum dan sesudah penyembuhan luka dari Februari sampai Mei 2019. Tiga puluh pasien dari ruang inap dengan luka menjadi kriteria inklusi sebagai responden. Responden direkrut oleh peneliti di rumah sakit dimana pasien sedang menjalani perawatan. Pengumpulan data menggunakan kuesioner data demografi dan lembar observasi penyembuhan luka. Pasien akan diberikan latihan selama 3 minggu. Penyembuhan luka diabetic pada pasien akan dikaji dan diukur sampai minggu ke tiga. Untuk menganalisis dan membandingkan data, distribusi frekuensi, mean (standar deviasi), dan paired t test dilakukan. Mean penyembuhan luka diabetik diantaranya 3.50, 2.90 dan 2.40 pada kelompok intervensi pada minggu pertama, kedua, dan ketiga secara berurutan. Perbedaan signifikan penyembuhan luka diabetic antara kelompok pre-test dan post-test (p=0.041). Suatu temuan penting bahwa area luka kaki diabetic semakin menurun pada orang yang melakukan senam. Temuan ini juga senam kaki sebaiknya dimasukkan dalam rencana perawatan ketika merawat pasien dengan luka kaki diabetik.